Standardized Reporting Guidelines for Emergency Department Syncope Risk Stratification Research - Sun, Benjamin C. (2012)
There is increasing research interest in the risk stratification of emergency department (ED) syncope patients. A major barrier to comparing and synthesizing existing research is wide variation in the conduct and reporting of studies. The authors wished to create standardized reporting guidelines for ED syncope risk stratification research using an expert consensus process. In that pursuit, a panel of syncope researchers was convened and a literature review was performed to identify candidate reporting guideline elements. Candidate elements were grouped into four sections: eligibility criteria, outcomes, electrocardiogram findings, and predictors. A two-round, modified Delphi consensus process was conducted using an internet-based survey application. In the first round, candidate elements were rated on a five-point Likert scale. In the second round, panelists re-rated items after receiving information about group ratings from the first round. Items that were rated by >80% of the panelists at the two highest levels of the Likert scale were included in the final guidelines. There were 24 panelists from eight countries who represented five clinical specialties. The panel identified an initial set of 183 candidate elements. After two survey rounds, the final reporting guidelines included 92 items that achieved >80% consensus. These included 10 items for study eligibility, 23 items for outcomes, 9 items for electrocardiogram abnormalities, and 50 items for candidate predictors. Adherence to these guidelines should facilitate comparison of future research in this area.